Composites technologies for 2020 : proceedings of the Fourth Asian-Australasian Conference on Composite Materials (ACCM-4) : University of Sydney, Australia, 6-9 July 2004 - Ye, L. (Lin), 1962-; Mai, Y. W., 1946-; Su, Z. (Woodhead, 2004)
The Asian-Australasian Association for Composite Materials (AACM) has been playing a leading role in the field of composite science and technology since its inception in 1997. AACM aims to encourage the interchange of knowledge in all aspects of composite materials both in the scientific and engineering communities. Following the success of the first three ACCM conferences ACCM 4 was held in Sydney, Australia, in July 2004. Composite technologies for 2020 provides current state-of-the-art achievements and recent advances in composite science and technologies bringing together leading experts and innovators in the field. Nearly 200 selected papers, classified under 18 different categories ranging from general manufacturing and processing techniques to the latest and hottest topics such as nano-composites and eco-bio composites. Together they represent an authorative documentation of current advances in the field of composite materials.